2015
DOI: 10.1155/2015/384860
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Androgen and Glucocorticoid Receptors in Bladder Cancer

Abstract: Bladder cancer is encountered worldwide having been associated with a host of environmental and lifestyle risk factors. The disease has a male to female prevalence of 3 : 1. This disparity has raised the possibility of the androgen receptor (AR) pathway being involved in the genesis of the disease; indeed, research has shown that AR is involved in and is likely a driver of bladder cancer. Similarly, an inflammatory response has been implicated as a major player in bladder carcinogenesis. Consistent with this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 123 publications
1
26
0
Order By: Relevance
“…High expression of GRα has been associated with indicators of less aggressive biological behavior in malignant neoplasms, such as smaller tumor size, early clinical stages, and higher survival rates of patients . These results have been attributed to the participation of GRα in immunoinflammatory responses, as well as cell proliferation and apoptosis . The mechanisms whereby GR modulates programmed cell death are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of GRα has been associated with indicators of less aggressive biological behavior in malignant neoplasms, such as smaller tumor size, early clinical stages, and higher survival rates of patients . These results have been attributed to the participation of GRα in immunoinflammatory responses, as well as cell proliferation and apoptosis . The mechanisms whereby GR modulates programmed cell death are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…5,10,11 These results have been attributed to the participation of GRα in immunoinflammatory responses, as well as cell proliferation and apoptosis. 8,12,13 The mechanisms whereby GR modulates programmed cell death are poorly understood. It has been shown that overexpression of GR triggers the death of tumor cells, 14,15 possibly by inhibiting the expression of the antiapoptotic proteins Bcl-2 and Bcl-xL.…”
Section: Introductionmentioning
confidence: 99%
“…Two drugs for the treatment of type II diabetes, rosiglitazone and pioglitazone, have been shown to induce bladder cancer [ 56 , 57 ], but their effect on miR144 or GRβ expression is unknown. Recent studies have revealed that there is a 3:1 incidence in men compared to women for bladder cancer, which may be mediated by the androgen receptor (AR) [ 4 ]. Presumably, there may be an interaction between AR and GRβ in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, glucocorticoids (GCs) have been used in bladder cancer for their protective properties against the toxic effects of chemotherapy [ 2 ]. GCs may cause resistance to cisplatin, which is a treatment commonly used for bladder cancer [ 3 , 4 ]. The GC receptor (GR) is expressed as different isoforms, GRα and GRβ, which are a result of alternative splicing of a single gene [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation